Gene expression and protein levels of GnRH isoforms and their cognate receptors in the stallion testis and spermatozoa - Douthit, Courtney Jacqueline (Kansas State University, 2016)
Gonadotropin-releasing hormone (GnRH-I), as well as its receptor, GnRHR-I, once thought to be localized solely to the hypothalamus and anterior pituitary, have since been detected in the testis of numerous mammals. Another isoform of GnRH, GnRH-II, has been isolated from the testis of numerous mammals and binds a specific receptor, GnRHR-II. Our objective was to establish whether GnRH-I and GnRH-II, along with their specific receptors, are produced and present in the equine testis. Testicular tissue was collected from colts < 2 yr (n = 5) and stallions ≥ 2 yr (n = 10) of age during routine castrations. Total RNA extracted from testicular tissue was reverse transcribed and cDNA was subjected to conventional PCR using gene specific primers for GnRH-I, GnRHR-I, GnRH-II, and GnRHR-II. Protein was extracted and subjected to dot blot and Western blot using antibodies directed against GnRH-I, GnRH-II, GnRHR-I, or GnRHR-II. Transcripts for both ligands and receptors were detected in all testes. Product identity was confirmed by sequencing, which also clarified that unusual band sizes were the result of alternative splicing of GnRHR-II, and the retention of an intron in the GnRH-II mRNA was discovered. Prepro-GnRH-I and prepro-GnRH-II protein was detected in all stallion testes via dot blot technique. On Western blots, testicular samples from colts (n = 4) had 3-fold greater GnRHR-I levels compared to stallions (n = 7; P < 0.022). Conversely, there was a tendency for GnRHR-II protein to be greater in tissue collected from stallions compared to colts (P < 0.0756). Finally semen was collected from mature stallions (9 to 18 yr; n = 4) and purified using a discontinuous gradient. By utilizing immunocytochemistry, GnRHR-II was localized to the connecting piece of mature stallion spermatozoa. This is the first report identifying GnRH-I and -II and their receptors in the equine testis and GnRHR-II on mature stallion spermatozoa. These decapeptide hormones may act via autocrine and/or paracrine signaling to affect steroidogenesis and spermatogenesis in the stallion testis.
Keywords: GnRH-I; GnRH-II; Testis; Equine; Animal Sciences (0475)